Advertisement Remove all ads

Prove That: `(2^(1/2)Xx3^(1/3)Xx4^(1/4))/(10^(-1/5)Xx5^(3/5))Div(3^(4/3)Xx5^(-7/5))/(4^(-3/5)Xx6)=10` - Mathematics

Prove that:

`(2^(1/2)xx3^(1/3)xx4^(1/4))/(10^(-1/5)xx5^(3/5))div(3^(4/3)xx5^(-7/5))/(4^(-3/5)xx6)=10`

Advertisement Remove all ads

Solution

We have to prove that `(2^(1/2)xx3^(1/3)xx4^(1/4))/(10^(-1/5)xx5^(3/5))div(3^(4/3)xx5^(-7/5))/(4^(-3/5)xx6)=10`

Let x = `(2^(1/2)xx3^(1/3)xx4^(1/4))/(10^(-1/5)xx5^(3/5))div(3^(4/3)xx5^(-7/5))/(4^(-3/5)xx6)`

`=(2^(1/2)xx3^(1/3)xx2^(2xx1/4))/(5^(-1/5)xx2^(-1/5)xx5^(3/5))div(3^(4/3)xx5^(-7/5))/(2^(2xx(-3)/5)xx3xx2)`

`=(2^(1/2)xx3^(1/3)xx2^(1/2))/(5^(-1/5)xx2^(-1/5)xx5^(3/5))div(3^(4/3)xx5^(-7/5))/(2^(2xx(-3)/5)xx3xx2)`

`=(2^(1/2+1/2+1/5)xx3^(1/3))/(5^(-1/5+3/5))div(3^(4/3-1)xx5^(-7/5))/(2^(-6/5+1))`

`=(2^((1xx5)/(2xx5)+(1xx5)/(2xx5)+(1xx2)/(2xx5))xx3^(1/3))/5^((-1+3)/5)div(3^(4/3-(1xx3)/(1xx3))xx5^(-7/5))/2^(-6/5+(1xx5)/(1xx5))`

`=(2^(5/10+5/10+2/10)xx3^(1/3))/5^(2/5)div(3^((4-3)/3)xx5^(-7/5))/2^((-6+5)/5)`

`=(2^(12/10)xx3^(1/3))/5^(2/5)div(3^(1/3)xx5^(-7/5))/2^(-1/5)`

`=(2^(12/10)xx3^(1/3))/(5^(2/5)/1)div(3^(1/3)xx5^(-7/5))/(1/2^(1/5))`

`=(2^(12/10)xx3^(1/3)xx1/5^(2/5))/(3^(1/3)/1xx1/(5^(7/5))xx2^(1/5)/1)`

`=2^(12/10)xx3^(1/3)xx1/5^(2/5)xx1/3^(1/3)xx5^(7/5)/1xx1/2^(1/5)`

`=2^(12/10)xx1/2^(1/5)xx3^(1/3)xx1/3^(1/3)xx1/5^(2/5)xx5^(7/5)/1`

`=2^(12/10)/2^(1/5)xx5^(7/5)/5^(2/5)`

`=2^(12/10-1/5)xx5^(7/5-2/5)`

`=2^(12/10-(1xx2)/(5xx2))xx5^((7-2)/5)`

`=2^((12-2)/10)xx5^(5/5)`

`=2^(10/10)xx5^(5/5)`

= 2 x 5

= 10

Hence, `(2^(1/2)xx3^(1/3)xx4^(1/4))/(10^(-1/5)xx5^(3/5))div(3^(4/3)xx5^(-7/5))/(4^(-3/5)xx6)=10`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Mathematics for Class 9
Chapter 2 Exponents of Real Numbers
Exercise 2.2 | Q 3.4 | Page 24
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×